Food Choices and COVID-19: A Study of Traditional Dietary Habits in Chandigarh, India - Das, Suraj; Mishra, Anindya Jayanta (Society & Sustainability, 2021)
The study aims to understand the traditional dietary habits during the COVID-19 pandemic and to comprehend the role of societal norms associated with gender in the context of Chandigarh, India. The present paper reports the findings from a cross-section survey conducted in September-October 2020 in Chandigarh in India. In total, there were 70 participants for the primary survey. A five-point Likert scale was used for the primary survey on a scale anchored with Strongly Agree (5) to Strongly Disagree (1). We conducted a Chi-square test and Regression Analysis to test the hypothesis. The result proved that socio-cultural and gender norms are significant for food choice during pandemics. The study will benefit the policymakers while framing the policy dealing with pandemic considering the local socio-cultural perspective. The sample size was very small. Therefore, the outcomes of the study may not be generalized for the whole population of Chandigarh, India.